I Dewa Putu Rai's Creative Process in Creating the Music Accompanying “Kumbang Atarung” Dance - Bisma, I Wayan Arya; Yudarta, I Gede (Institut Seni Indonesia Denpasar, 2024)
This study was conducted to explore creativity in the dance’s accompanyment musical work called